Multi-Dimensional Identities of the Hispanic Population in the United States - Francisca M. Antman (Institute of Labor Economics (IZA), 2021)
This essay discusses the multi-dimensional identities of the Hispanic population in the United States as represented in current surveys. It reviews some of the critical barriers in data collection methods that limit research studies on this population. Solutions are suggested that would improve the collective understanding of this population and thus allow policymakers to better address the challenges faced by this large and diverse group of people.
Keywords: J15; Z13; 330; Hispanic/Latino; ethnicity; race; identity